New product development in brazilian technology-based small and medium enterprises - Toledo, José Carlos de; Mendes, Glauco Henrique de Sousa; Jugend, Daniel [UNESP]; Silva, Sérgio Luís da (Editora Cubo, 2013)
This article examines new product development (NPD) in small and medium-sized Brazilian enterprises (SMEs) in two technology-based industries: medical devices and process control automation devices. A conceptual model that categorizes factors that contribute to the success of a new product was established. The data were collected from a sample of 62 Brazilian SMEs. The conceptual model was tested to examine the relationships between NPD practices and new product success. Data analysis reveals that new product success in medical device companies is related to organizational characteristics such as NPD proficiency and marketing skills; while in process control automation device companies, they deal in a large degree with product differentiation, innovation and capability to analyze the targeted market. Due to the relatively small sample size, caution should be exercised when interpreting the results.
Keywords: New product development; Success critical factors; Small and medium enterprises; Medical device industry; Process control automation device industry